ETUDE PHYTOCHIMIQUE DE QUELQUES VARIETES DE BLE TENDRE (TRITICUM AESTIVUM) ET D’ORGE (HORDEUM VULGARE) ET LEURS ACTIVITES BIOLOGIQUES - Ghania, Chaib; Amira, Bouchelaleg; Romeissa, Talbi (European Scientific Journal, ESJ, 2015)
Our research focuses on the photochemical study of polyphenols extracted from the leaves of the three varieties (MD, MP and FA) of soft wheat (Triticum aestivum) and the three varieties (Jaidore, Rihane and Saida) of barley (Hordeum vulgare), during two stages of their life cycle (bolting and flowering), and to test their biological activities (antibacterial: E.coli and antifungal: Aspergillums and Penicillium). The results of the quantitative study of ethanol extracts show the existence of a variability intra and inter varietal. The qualitative study of polyphenols begins with repartitions between four solvents with different polarities. This leads to obtain different phases. Their compositions are identified by thin layer chromatography, which show’s that the majority of polyphenols are flavonoids of flavones and flavonols type. The results of antibacterial activity showed that the extract of each variety has a significant inhibitory effect on the growth of E. coli. On the contrary antifungal activity reveals no effect on Aspergillums and Penicillium. Finally, instead of classifying soft wheat and barley as cereal or purely food plants, we could oriente their exploitation to medicinal plants.